2018
DOI: 10.1101/316299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repression of ferritin light chain translation by human eIF3

Abstract: 16Iron is essential to life, but excess iron is detrimental as it catalyzes reactive hydroxyl radical 17 production. To prevent iron toxicity, intracellular iron homeostasis is regulated by ferritin, a 18 protein complex composed of a mixture of two subunits: ferritin light chain (FTL) and ferritin 19 heavy chain (FTH). Ferritin expression is regulated post-transcriptionally by the iron response 20 proteins (IRPs), which bind an RNA hairpin -the iron responsive element (IRE) -located in 21 the FTL and FTH mRNA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Recently, it has been shown that eIF3 acts as a repressor of Ftl1 translation in vitro. 33 Our results confirm the link between eIF3 and Ftl1 and, for the first time, provide evidence for the repression of Ftl1 translation by eIF3 in vivo in the liver.…”
Section: Resultssupporting
confidence: 84%
“…Recently, it has been shown that eIF3 acts as a repressor of Ftl1 translation in vitro. 33 Our results confirm the link between eIF3 and Ftl1 and, for the first time, provide evidence for the repression of Ftl1 translation by eIF3 in vivo in the liver.…”
Section: Resultssupporting
confidence: 84%
“…eIF3 interacts with a stem-loop structure in the coding sequence of H4 mRNA It was previously established that human translation initiation factor eIF3 can target mRNAs in a transcriptspecific manner and can function as an activator or repressor of translation (19)(20)(21). The majority of the mRNAs identified contain a single eIF3-binding site predominantly located within 5'UTR RNA structural elements (19).…”
Section: Resultsmentioning
confidence: 99%
“…The translation of several additional mRNAs is repressed by eIF3. This is the case for the cell proliferation regulator BTG1 (19), ferritin light chain (FTL) mRNA (21), and msl-2 mRNA in Drosophila melanogaster (66). How eIF3 binding can contribute to the negative translation regulation of an mRNA and modulation of histone translational regulation in particular is unclear at this stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has begun to reveal that different eIF3 subunits can selectively regulate translation in a manner depending on cell type, mRNA targets, and post-translational modification. Interaction of eIF3 RNA-binding subunits with specific 5′UTR stem-loop structures of mRNAs can trigger a translational switch for cell proliferation in human 293T cells (Lee et al 2015), and can also act as a translational repressor, such as the case for human Ferritin mRNA (Pulos-Holmes et al 2019). Under cellular stress, such as heat shock, the eIF3 complex circumvents cap-dependent protein translation initiation and recruits ribosomes directly to m6A marks within the 5′UTR of mRNAs encoding stress response proteins (Meyer et al 2015).…”
Section: Introductionmentioning
confidence: 99%